Migration and Development in India - Datta, Amrita (Taylor & Francis, 2026)
This book deals with a wide range of issues related to rural-urban migration in the context of neoliberal economic development in India. Focusing on three core areas, first it traces state discourses on rural-urban migration in India since the 1930s critically analysing its industrial, labour, rural and urban programmes, and policies. Second, through data on longitudinal surveys undertaken in rural Bihar in 1999, 2011 and 2016, it examines changes in patterns of migration and sources of income; estimates determinants and impacts of migration. Third, based on fieldwork in the village and the city, it presents an in-depth account of a rural-urban migration stream in contemporary India. It shows how, contrary to the results of conventional data sources such as the Census and NSSO, that mobility is high in rural Bihar, and has significantly increased over time as a result of rising labour demand in distant urban markets elsewhere in India. Further, it also provides evidence of decoupling of agriculture from the ‘rural’ in India. Combining quantitative and qualitative methods in development research, this book will be of great interest to scholars and researchers of development studies, migration studies, development economics, sociology, demography, public policy, and South Asian studies.